2011
DOI: 10.1039/c1ay05231d
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible self-assembled monolayer platform based on (3-glycidoxypropyl)trimethoxysilane for total cholesterol estimation

Abstract: An electrochemical cholesterol biosensor has been fabricated via covalent immobilization of cholesterol oxidase and cholesterol esterase (ChOx and ChEt) onto a biocompatible self assembled monolayer (SAM) of (3-glycidoxypropyl)trimethoxysilane (GPTMS) fabricated onto an indium tin oxide (ITO) electrode. The ChOx/GPTMS/ITO bioelectrode has been characterized using Fourier transform infrared spectroscopy (FTIR), contact angle measurements (CA), atomic force microscopy (AFM), electrochemical impedance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Different design strategies have been utilised for the development of electrochemical cholesterol biosensors including oxidation by mediated ChOx [5][6][7][8][9][10] or hydrogen peroxide monitoring by horse radish peroxidase 11,12 or by inorganic catalysts 13 and nanostructures [14][15][16] . Despite of the variety of reported cholesterol electrochemical biosensors 4 , only few of them have been shown to operate in whole blood [17][18][19] . An amperometric biosensor based on ChOx entrapped inside a composite polypyrrole-hydrogel membrane showed excellent correlation with results obtained by the standard method 17 for total cholesterol determination in cholesterol esterase (ChEt) pretreated serum samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different design strategies have been utilised for the development of electrochemical cholesterol biosensors including oxidation by mediated ChOx [5][6][7][8][9][10] or hydrogen peroxide monitoring by horse radish peroxidase 11,12 or by inorganic catalysts 13 and nanostructures [14][15][16] . Despite of the variety of reported cholesterol electrochemical biosensors 4 , only few of them have been shown to operate in whole blood [17][18][19] . An amperometric biosensor based on ChOx entrapped inside a composite polypyrrole-hydrogel membrane showed excellent correlation with results obtained by the standard method 17 for total cholesterol determination in cholesterol esterase (ChEt) pretreated serum samples.…”
Section: Introductionmentioning
confidence: 99%
“…An amperometric biosensor based on ChOx entrapped inside a composite polypyrrole-hydrogel membrane showed excellent correlation with results obtained by the standard method 17 for total cholesterol determination in cholesterol esterase (ChEt) pretreated serum samples. Kumar et al have developed an electrochemical biosensor, based on covalent coimmobilisation of ChOx and ChEt onto an electrode modified with a biocompatible self-assembled monolayer for total cholesterol quantification in undiluted serum samples 18 . Zhu et al have reported a biosensor based on direct electron transfer of ChOx immobilised on multiwalled carbon nanotubes decorated with gold nanoparticles for free cholesterol measurements in entire human serum 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In one of the study, noncytotoxicity of GPTMS was validated by the assessment of cytocompatibility of hybrids of gelatin-GPTMS and chitosan-GPTMS in an in-vitro study (Ren et al, 2002a). In another study, biocompatibility of GPTMS SAM was confirmed using both bacterial culture (E.coli DH5a, Gram negative bacteria) and plant tissue culture (wheat seed) (Kumar et al, 2011).…”
Section: Cytotoxicity Test Resultsmentioning
confidence: 98%
“…Furthermore, the reduction wave intensity was decreased to a large extent. These observations indicated that Hy monolayers were successfully grafted over ATU/Cu surface [40][41][42]. …”
Section: Cyclic Voltammetric Studiesmentioning
confidence: 85%